State Court Organizations, 2004 (United States) ([Verlag nicht ermittelbar], 2006)
This data collection provides detailed comparative information about the structure, policies, and procedures of state-wide trial and appellate court systems for the 50 states, the District of Columbia, and Puerto Rico in the United States as of June 31, 2004. Information gathered includes: the number of courts and judges, judicial selection, governance of court systems (including judicial funding, administration, staffing, and procedures), jury qualifications and verdict rules, and processing and sentencing procedures of criminal cases. Data collection was carried out by the National Center for State Courts.